If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6 = 1 + 6 Reorder the terms: -6 + 8x = 1 + 6 Combine like terms: 1 + 6 = 7 -6 + 8x = 7 Solving -6 + 8x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8x = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 7 + 6 8x = 7 + 6 Combine like terms: 7 + 6 = 13 8x = 13 Divide each side by '8'. x = 1.625 Simplifying x = 1.625
| -3y+3-2y=8+2y | | 21(19-x)=15(5x-1) | | 125.00s+5.75=228.50 | | 40+15+.25(100)=45+.35(100) | | 6x^2+3x+8=0 | | 3(x-3)-4x=7x+5 | | 4(x+2)+6=2x | | -5=n+4 | | =a^2-6a+9 | | 4x-5=6x+17 | | 3m-6(7m-4)=336 | | 15=5(3q-10)-5q | | 2x(p+8)=90 | | 3(x-2)=-12 | | 39=-2(22-z)+3(z-4) | | 2x-3=3(5x-2) | | 5(2x+3)-2=45 | | 0.5x-12=4 | | 3x+1=4x+1 | | 14x-(7x-3)=66 | | 4-z=5 | | 4x^2+72x=0 | | 5=-4y | | x+1.5x+90=180 | | -5x+3x=17+7 | | 3x-10+7x+20=90 | | -8.9y-10.11=74.44 | | 2b^2(b^2-9)=0 | | 5x-8x+7=x-8+15 | | 34.8k+.2(1k-4)=1.2-9(2-3k) | | -10(x-5)-8=72 | | 4x-20=6x+14 |